Polymorphisms in HSD17B1: Early Onset and Increased Risk of Alzheimer's Disease in Women with Down Syndrome. (4th March 2012) - Lee, Joseph H.; Gurney, Susan; Pang, Deborah; Temkin, Alexis; Park, Naeun; Janicki, Sarah C.; Zigman, Warren B.; Silverman, Wayne; Tycko, Benjamin; Schupf, Nicole
Abstract : Background/Aims . Genetic variants that affect estrogen activity may influence the risk of Alzheimer's disease (AD). In women with Down syndrome, we examined the relation of polymorphisms in hydroxysteroid-17beta-dehydrogenase ( HSD17B1 ) to age at onset and risk of AD. HSD17B1 encodes the enzyme 17β-hydroxysteroid dehydrogenase (HSD1), which catalyzes the conversion of estrone to estradiol. Methods . Two hundred and thirty-eight women with DS, nondemented at baseline, 31–78 years of age, were followed at 14–18-month intervals for 4.5 years. Women were genotyped for 5 haplotype-tagging single-nucleotide polymorphisms (SNPs) in the HSD17B1 gene region, and their association with incident AD was examined. Results . Age at onset was earlier, and risk of AD was elevated from two- to threefold among women homozygous for the minor allele at 3 SNPs in intron 4 (rs676387), exon 6 (rs605059), and exon 4 in COASY (rs598126). Carriers of the haplotype TCC, based on the risk alleles for these three SNPs, had an almost twofold increased risk of developing AD (hazard ratio = 1.8, 95% CI, 1.1–3.1). Conclusion . These findings support experimental and clinical studies of the neuroprotective role of estrogen.